Denoting by "I" the identity operation, we have
"(T + I) (x, y, z) = (0, x, 3x + 2y + 2z) \\, , \\\\ \n(T + I)^2 (x, y, z) = (0, 0, 8x + 4y + 4z) \\, , \\\\\n(T - I) (x, y, z) = (- 2 x, x - 2 y, 3x + 2y) \\, ."Combining these equations together, we obtain
"(T - I) (T + I)^2 (x, y, z) \\\\ {} = (T - I) (0, 0, 8 x + 4 y + 4 z) = (0, 0, 0) \\, ."Hence, "T" satisfies the polynomial "p (x) = (x - 1) (x + 1)^2". Considering "v = (1, 0, 0)", we have
"T (v) = (-1, 1, 3) \\, , \\quad T^2 (v) = (1, -2, 2) \\, ."The vectors "v", "T (v)" and "T^2 (v)" are linearly independent; hence, the minimal polynomial of "T" has degree three. Since "p (x)" has degree three and is a monic polynomial (its leading coefficient is equal to 1), and since "p (T) = 0", it is the minimal polynomial.
Comments
Leave a comment